Credit Borrower Sector of Economy and Credit Risk For Banks - Stępińska, Joanna (Journal of Finance and Financial Law, 2024)
The purpose of the article. Business entities in different industries operate differently. Therefore, different sectors are characterized, among other things, by different profitability, the need for external financing, and, consequently, a different level of risk of default on credit commitments to banks. Borrowers from specific industries may be, from the perspective of banks' interests, better or worse customers and contribute to strengthening or weakening the quality of their credit portfolios. The purpose of the article is to compare sections of the economy in terms of the credit risk accompanying banks lending to them. The analysis conducted will be used to verify the hypothesis that industries are significantly different in terms of banks' credit risk related to credits they grant. Methodology. The article supplements the literature with a cross-sectional analysis of economic sectors and includes an assessment of the differentiation of each of them in terms of their economic condition and the associated potential risk of banks lending to their respective industries. The first section of the article presents a literature review covering the issue of comparing the risk of operating in different industries, and the second presents the classification of sections of the economy according to the Polish Classification of Activities (PKD) . The third part presents data from the National Bank of Poland NBP on the repayment of credits in various industries. The fourth section of the article presents the characteristics of each section of the economy. The size of the operating of each industry, taking into account the size of its revenues and the number of enterprises, as well as the scale of investment and the demand for credit and loans in each section of the economy are presented. The cost level index, debt-to-equity ratio, the share of credit s and credits of each section in relation to equity are also examined. The relationships between: debt and financial results of sectors, financial costs and credit, and financial costs and net financial results of industries are also characterized in this chapter. In addition, the profitability and liquidity of economic sections were examined. The fourth chapter also analyzed data on bankruptcy and restructuring proceedings opened by section of the economy. Results of the research. The assumptions and results of the analysis of the risk of credit defaults by each section of the economy are presented in the last section of the article. In addition, the results of the analysis carried out in the article are discussed and compared with NBP data on the share of credits in phases 2 and 3 in each industry. The conclusion of the study is that industries are significantly different in terms of credit risk from the perspective of the banks providing them with financing.